2004
DOI: 10.1542/peds.114.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Special Supplemental Nutrition Program for Women, Infants, and Children Participation and Infants’ Growth and Health: A Multisite Surveillance Study

Abstract: Infants < or =12 months of age benefit from WIC participation. Health care providers should promote WIC utilization for eligible families and advocate that WIC receive support to reduce waiting lists and eliminate barriers that interfere with access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 28 publications
3
80
2
1
Order By: Relevance
“…[68][69][70][71][72][73] For non-HIV infected populations, federally funded food assistance programs (e.g., the Supplemental Nutrition Assistance Program and Special Supplemental Nutrition Program for Women, Infants, and Children) have been shown to have a protective effect on pregnancy outcomes among women, 74,75 birthweight outcomes for infants, 76 and nutritional outcomes for young children. 77,78 Limited research has examined health-care utilization among program participants. 79 Several studies in the general population have found equivocal 80,81 or detrimental 82 health outcomes associated with program participation; these studies are difficult to interpret because selection bias was probably not at all or only partially controlled.…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70][71][72][73] For non-HIV infected populations, federally funded food assistance programs (e.g., the Supplemental Nutrition Assistance Program and Special Supplemental Nutrition Program for Women, Infants, and Children) have been shown to have a protective effect on pregnancy outcomes among women, 74,75 birthweight outcomes for infants, 76 and nutritional outcomes for young children. 77,78 Limited research has examined health-care utilization among program participants. 79 Several studies in the general population have found equivocal 80,81 or detrimental 82 health outcomes associated with program participation; these studies are difficult to interpret because selection bias was probably not at all or only partially controlled.…”
Section: Discussionmentioning
confidence: 99%
“…19 WIC has undergone many evaluations, consistently showing positive effects on dietary quality, health outcomes (e.g., birth weight, anemia), and health service utilization. [20][21][22] Rigorous evaluations are diffi cult, however, because of the program's wide coverage and the fact that eligible non-participants are necessarily (and unobservably) different from participants.…”
Section: Integrated Approachesmentioning
confidence: 99%
“…[1][2][3] Children from disadvantaged households are often affected by food insecurity (FI), defined as "the lack of access to enough food to fully meet basic nutritional needs at all times due to lack of resources." [4][5][6][7][8] Many Americans experience FI or marginal food security 9 ; 21% of all US households with children are food insecure, with households in poverty known to be at greatest risk. 10 Primary care clinics in academic medical centers often care for children from these high-risk, underserved populations.…”
Section: Discussionmentioning
confidence: 99%
“…Infants are especially vulnerable to FI-related health consequences, including anemia, developmental delay, acute illnesses, and increased hospitalizations. [6][7][8][14][15][16][17][18] Still, given normal growth parameters for the vast majority of food-insecure infants, detecting FI in the clinical setting can be difficult. 12 Efforts to increase identification of FI in our PPCC have been successful, 19 but an intervention to respond to FI when identified was deemed necessary.…”
Section: Discussionmentioning
confidence: 99%